Amino‐Modified Poly (l–lactic Acid) Nanofibers Enable pH‐Stimulated Drug Release and NIR Real‐Time Detection. Issue 2 (3rd January 2022) - Cao, Zhi‐Kai; Zhang, Jun; Yu, Yan‐Chao; Wang, Bing‐Chang; Bai, Xiao‐Han; Yang, Jun; Liang, Yi‐Tao; Ramakrishna, Seeram; Long, Yun‐Ze
Abstract: Stimulus‐responsive nanofibers can adjust the speed of drug delivery, and real‐time monitoring elucidates the relationship between drug release and therapeutic efficacy. Both of these advantages have great potential in clinical therapy. However, the complex preparation of current stimulus‐responsive drug‐loaded nanofibers leads to low drug‐loading levels, limiting their widespread applications. In this study, we prepared pH‐responsive drug‐loaded nanofibers with fluorescence monitoring properties using the electrospinning method. A representative drug of DOX was loaded onto the nanofibers. The degradable flexible nanofibers modified by amino groups attained higher drug loading and controlled drug release. Precisely, the rate of drug release varies with different pH. Faster release speed occurs in the tumor microenvironment with faintly acidic conditions than in healthy tissues with neutral conditions. The pH‐responsive mechanism was due to hydrazone bonds between the amino groups and DOX molecules, which FTIR confirmed. In addition, these pH‐responsive nanofibers with intense upconversion fluorescence enable more sensitive monitoring, whereas weak luminescence cannot achieve. Abstract : Electrospun NaYF4 :Yb 3+, Er 3+ @PLLA nanofibers introduce pH‐sensitive functional groups and are load with DOX drug. After the DOX release, the photoluminescence of nanofiberat 550 nm becomes stronger under NIR 980 nm exciatation, which could be used to monitor the release of drug in real time.